History of Type 1 Diabetes Mellitus And Current Treatment Methods - Yusufoğlu, Sema; Gacar, Gülçin (General Internal Medicine V, 2023)
Diabetes mellitus (DM) is a lifelong disease that develops due to the ineffectiveness or deficiency of endogenous insulin, accompanied by acute and chronic complications. Diabetes Mellitus is among the most common diseases throughout the history of the world. According to the 2021 data of the International Diabetes Federation (IDF), while there are more than 537 million people with diabetes today, it is predicted that this figure will increase by 51% to 700 million in 2045 (1). Type 1 diabetes develops due to autoimmune damage of beta cells responsible for insulin in the pancreas, has hereditary causes in most cases, and is frequently seen in childhood. Type 1 diabetes constitutes a large part of this 463 million that cannot be ignored, and this number is expressed in millions. Due to the amount of glucose in the peripheral blood that is not treated and cannot be controlled, complications may occur at a level that can completely change the living standards of individuals. For example, diabetic ketoacidosis may enter hyperosmolar coma in the acute period, or complications such as heart and kidney diseases, visual defects, paralysis may develop in the long term, and even losses may occur. In Type 1 Diabetes Mellitus, the need for insulin, which cannot be produced by the beta cells in the pancreas, is provided with the help of an injection or pump, which is called classical treatment. At the same time, studies carried out with the help of multidisciplinary biotechnology today wink at promising radical treatments. These potential treatments are promising for individuals. Our review provides a broad perspective on the definition and history of type 1 Diabetes Mellitus and all biotechnological treatment processes, both classical and promising.